The cost of capital of the financial sector - Tobias Adrian; Evan Friedman; Tyler Muir (Federal Reserve Bank of New York, 2015)
Standard factor pricing models do not capture well the common time-series or cross-sectional variation in average returns of financial stocks. We propose a five-factor asset pricing model that complements the standard Fama and French (1993) three-factor model with a financial sector ROE factor (FROE) and the spread between the financial sector and the market return (SPREAD). This five-factor model helps to alleviate the pricing anomalies for financial sector stocks and also performs well for nonfinancial sector stocks compared with the Fama and French (2014) five-factor model or the Hou, Xue, and Zhang (2014) four-factor models. We find that the aggregate expected return to financial sector equities correlates negatively with aggregate financial sector ROE, which is puzzling, as ROE is commonly used as a measure of the cost of capital in the financial sector.
Keywords: G12; G21; G24; G32; 330; cost of capital; financial intermediation; asset pricing; capital structure